Justice overdue - Childs, Lisa (Love inspired cold case, 2021)
Not enough clues. Too many secrets. And someone out to silence them... Three decades. Untold victims. A Michigan town in fear. It's a case Sheriff Hogan Moore promised his father he would crack on his own. But when DNA expert Eve Collins finds a hidden lead, he must team up with her to uncover the truth. Now with devastating secrets--and a determined killer--ambushing them at every turn, will they live to tell?